Co-infection of hepatitis E virus, Clonorchis sinensis, and Escherichia coli: A case report - Zhang, Lu; Wang, Xiaohao; Zhang, Jing; Wang, Zhongrong; Cai, Dachuan (Frontiers in Cellular and Infection Microbiology, 2023)
Hepatitis E virus (HEV) is a common cause of acute hepatitis that threatens human health worldwide. With the popularization of detection technology, the reports of hepatitis E have gradually increased. Here, we present a rare case of co-infection with Hepatitis E virus, Clonorchis sinensis and Escherichia coli. A 52-year-old-aged male was hospitalized because of fatigue, jaundice, nausea for more than 2 weeks. Laboratory tests showed elevated bilirubin and transaminitis, HEV-IgM was positive, HEV-RNA could be detected. Moreover, parasites were found in the biliary drainage and the biliary culture suggested Escherichia coli. The patient was effectively treated with praziquantel, imipenem, and hepatoprotective drugs and his clinical symptoms relieved after 2months.